Genetic diversity analysis of Ghoongroo pig based on microsatellite markers - SAHOO, NIHAR RANJAN; NESA, NASHIMUN; NASKAR, SOUMEN; BANIK, SANTANU; PANKAJ, PRABHAT KUMAR (The Indian Journal of Animal Sciences, 2015)
An attempt was made to measure the genetic variation available within Ghoongroo pigs, a prized germplasm in terms of high growth and multiplication rate among the indigenous varieties, using 22 FAO-ISAG microsatellite markers. The data were analyzed applying different software to estimate the various measures of genetic diversity. The average number of observed allele was 8.18±0.62 and the effective average number of allele was 4.39±0.26. The observed heterozygosity ranged from 0.4 to 0.96 and the expected heterozygosity from 0.55 to 0.85. Average PIC value ranged from 0.55 (S0026) to 0.85 (S0068) with the average value 0.75±0.02. The mean F value was 0.07±0.04. There was no genetic bottleneck observed in the studied population. A total of 45 private alleles were observed which can be used as breed specific markers. The results suggested that all the microsatellite markers were highly polymorphic and suitable for molecular characterization of Ghoongroo pig. There was substantial genetic variation and polymorphism across the studied loci. The low inbreeding observed was a favourable parameter to formulate the appropriate breeding strategies to enhance heterozygosity in the population.